Reference crust-mantle density contrast beneath antarctica based on the vening meinesz-moritz isostatic inverse problem and crust2.0 seismic model (2013)
We estimate the crust-mantle (Moho) density contrast beneath Antarctica based on solving the inverse problem of isostasy and using the constraining information from the seismic global crustal model (CRUST2.0). The solution is found through applying the least-squares adjustment by elements method. The global geopotential model (GOCO02S), the global topographic/bathymetric model (DTM2006.0), the ice-thickness data for Antarctica (assembled by the BEDMAP project), and the global crustal model (CRUST2.0) are used to compute the isostatic gravity anomalies. Since the CRUST2.0 data of crustal structures under Antarctica are not accurate (due to the lack of seismic data), the (reference) crust-mantle density contrast is determined with respect to the homogenous crustal model of reference constant density 2670 kg/m3. The estimated reference crust-mantle density contrast is between 160 and 682 kg/m3. The density contrast spatial distribution corresponds with major features of the Antarctic continental and surrounding oceanic tectonic plate configuration. The maxima exceeding 500 kg/m3 are found throughout the central part of East Antarctica with the extension under the Transantarctic mountain range. The crust-mantle density contrast beneath West Antarctica decreases to 400-500 kg/m3 except for the local maxima up to ~550 kg/m3 in the central Antarctic Peninsula.